An extended Peng‐Robinson equation of state for carbon dioxide solid‐vapor equilibrium. Issue 2 (14th March 2013) - Martynov, Sergey; Brown, Solomon; Mahgerefteh, Haroun
Abstract The Peng‐Robinson equation of state (PR EoS) for liquid‐vapor equilibrium is extended to model the solid‐vapor (sublimation) and solid‐liquid (melting) phase equilibria for carbon dioxide (CO2). The sublimation behavior is modeled through the re‐formulations of the empirically based analytical expressions for the two temperature dependent parameters, a and b in the PR EoS. The melting phase behavior on the other hand is modeled by the coupling of the original and the extended PR EoS and equalization of solid and liquid phase fugacities. Analytical expressions derived based on the extended PR EoS are used to determine thermodynamic and phase equilibrium derivative properties for solid/vapor CO2. These include internal energy, enthalpy, heat capacity, thermal expansion, and isothermal compressibility coefficients as well as the adiabatic speed of sound. In most cases good agreement with the available experimental data is obtained covering the pressure and temperature ranges 0.1–100 MPa and 100–300 K. A pressure/temperature phase equilibrium diagram for solid‐liquid‐vapor CO2 is constructed to demonstrate the overall performance and the limitations of the two EoS as compared to the experimental data spanning the triple point up to 100 MPa pressure. It is shown that the application of the PR EoS along the CO2 sublimation line gives rise to significant errors. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd